Design of Round Radial Mode Piezoelectric Transformer for Lamp Ballast Applications - Ghusoon Muhsin Ali; Ghanim Abd Al-Kareem Al-Rubyai (Journal of Engineering and Sustainable Development, 2006)
In conventional electronic ballast for a fluorescent lamp, inductor-capacitortransformer tank circuit is used. A Piezoelectric Transformer (PT) can potentially be used to replace such a tank circuit to save space and cost. In the past, ballast design using a PT requires selecting a PT from available samples which are normally not matched to the specific application and therefore resulting in poor performance, also piezoelectric transformer design has been difficult due to the complex interaction between the physical and electrical circuit characteristics. In this research, a design procedure has been developed for designing a PT tailored for 220-V 40-W electronic ballast with high efficiency (90%) and Zero-Voltage-Switching (ZVS) for the semiconductors without the use of any external inductance. In this design a round radial-mode piezoelectric transformer (Transoner) was used and to achieve an optimum solution, a 3-D graphic to circuit requirement is used which allows the engineer to design according to the circuit criteria, the design is programmed by using the MATLAB package.